The Toyota Production System (TPS) : ett verktyg för att skapa effektiv och lönsam produktion - Fries, Carl Johan (SLU/Dept. of Economics, 2012)
Many companies are currently working to optimize and streamline their processes and production lines to achieve higher profitability. In increasingly competitive markets, companies are working to find solutions to increase the value of their production with such a small use of resources as possible. A tool used to accomplish this is the Lean management system. Lean comes from the production system that Toyota has been developing since the early 1900's, The Toyota Production System (TPS). The Lean philosophy helps companies, by working towards continuous improvement in its operations, to achieve higher customer satisfaction, more efficient production and ultimately higher profitability. Many companies are working to implement Lean in their organization. But there are many who fail to implement a complete change towards Lean. That's because many companies use only a few theories and tools as described in Lean, which is not enough. This leads to the purpose of this study which is to examine how Lean tools can be used to achieve more efficient operations, increased customer satisfaction and improved profitability. In addition to this, Toyota's assertion that there is always room for continuous improvement within a business is examined to find out if it’s reasonable or not. To get answers to the above stated problem, a theoretical study of Lean and its principles and tools was conducted. In addition, a short study of process, organization and motivation theory to complement Lean theories was done. The theoretical findings were analyzed and then put in relation to an empirical study to link Lean to a specific case. The conclusions of these studies are that Lean and its theories can help companies increase efficiency, increased customer satisfaction and ultimately increased profitability. Strong commitment and deep understanding is required of both the company management as of the employees in the organization. Only when the organization has the full understanding of the current situation, why a change in the business is required and the aim with the change is understood, you can put Lean into effective use. Lean is a powerful tool for an organization that wants to change and develop their business.